Degradation and deformation of latex and non-latex orthodontic elastics - Oliveira, Pedro Lima Emmerich; Matsumoto, Mírian Aiko Nakane; Faria, Gisele [UNESP]; Romano, Fábio Lourenço (My University, 2017)
Background: Intermaxillary elastics are widely used in corrective orthodontic treatment particularly for the interdigitation of buccal segments and the correction of the midline. However, latex has been known to cause allergy, which may restrict elastic use. As alternative materials, non-latex elastics are available. However, clinicians must be aware of their mechanical properties, especially those of deformation and force degradation that affect these materials over time. Objectives: The aim of this study was to compare force degradation and deformation of 3/16 non-latex and latex elastics supplied by several manufacturers. Materials and methods: Special acrylic plates were fabricated to incorporate orthodontic brackets to which elastics were attached and stretched to a distance of approximately 20 mm. The internal diameter and force magnitude of each elastic was measured at time intervals of 0, 24, 72 and 504 hours. The samples were stored in artificial saliva at room temperature during the entire experimental period. Results: Latex elastics showed smaller and more uniform deformation than the non-latex elastics. The non-latex elastics showed greater degradation at all time intervals (p < 0.001). The Morelli brand delivered greater force than other brands for both the latex and non-latex elastics at all time intervals (p < 0.05). The G&H latex elastics showed greater force degradation in comparison with the other brands (p < 0.05). The evaluation of the Dentaurum and Orthopli non-latex elastics showed greater degradation (p < 0.05). Conclusions: The non-latex elastics showed greater force degradation than the latex elastics. Of the latex elastics, G&H showed greater force degradation, and for the non-latex elastics, those made by Dentaurum and Orthopli degraded most.